2009
DOI: 10.1021/mp8002368
|View full text |Cite
|
Sign up to set email alerts
|

Improved Bone Delivery of Osteoprotegerin by Bisphosphonate Conjugation in a Rat Model of Osteoarthritis

Abstract: This study investigated the delivery of a model therapeutic protein, namely, osteoprotegerin (OPG), to bone sites in an animal model of osteoarthritis. The OPG was chemically conjugated to a "bone seeking" thiol-bisphosphonate (thiolBP) via a disulfide linkage. The BP conjugates of OPG were shown to display a higher hydroxyapatite affinity in vitro as compared to unmodified OPG. After intravenous injection, the bone uptake of OPG-thiolBP conjugate was increased 2-fold over that of control OPG under conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…Osteoprotegerin Disulfide Prevention of bone resorption [32] Delivery of BP-modified protein was increased in osteoarthritis model Thiol-BP Salmon calcitonin Amide [33] Conjugate-induced reduction in loss of bone mineral density and bone volume in osteoporotic rats Carboxyl-BP Catalase Amide Reduce ROS in bone [34] Bone-specific anticancer activity was not clear BPpolymer…”
Section: Amidementioning
confidence: 99%
See 1 more Smart Citation
“…Osteoprotegerin Disulfide Prevention of bone resorption [32] Delivery of BP-modified protein was increased in osteoarthritis model Thiol-BP Salmon calcitonin Amide [33] Conjugate-induced reduction in loss of bone mineral density and bone volume in osteoporotic rats Carboxyl-BP Catalase Amide Reduce ROS in bone [34] Bone-specific anticancer activity was not clear BPpolymer…”
Section: Amidementioning
confidence: 99%
“…Despite that all bisphosphonated proteins showed high binding to HAP disks in vitro as compared to the control proteins, intravenous injection of only the amide-linked fetuin-BP resulted in its increased delivery to bone in rats. A significant advantage of BP conjugation for delivery to osteoarthritic bones was demonstrated with osteoprotegerin (OPG) that was linked to BP via a disulfide linkage [32]. OPG is a soluble circulating glycoprotein that interrupts receptor activator of nuclear factor kappa-B ligand--RANK intracellular signaling that is essential for osteoclast formation.…”
Section: Bp-functionalized Proteins (Growth Factors Enzymes)mentioning
confidence: 99%
“…Nonetheless, our experience with BP conjugative strategies has amply demonstrated that each protein or peptide will behave differently during the conjugation process, with unique solubility, stability, and bioactivity issues (Doschak et al, 2009;Uludag et al, 2000a,b;Gittens et al, 2003). Accordingly, one "generalized" conjugation procedure will not work as a universal reaction scheme for all therapeutic peptides and proteins and individualized strategies will need to be considered and employed on a "case-by-case" basis for individual peptide or protein candidates, as previously hypothesized (Hirabayashi and Fujisaki, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…13 Bisphosphonate derivatives have been used to deliver therapeutic compounds such as estradiol, diclofenac, and osteoprotegerin to bones by conjugation. [14][15][16][17] Results of these previous studies suggest that the conjugation of bisphosphonate is a promising approach for delivering catalase to the bones in individuals with bone metastasis. In this study, we conjugated bovine liver catalase with di(bisphosphonate) 3,5-di(ethylamino-2,2-bisphosphono)benzoic acid (Bip), a bisphosphonate derivative that has two bisphosphonate groups in one molecule, 18 to endow the enzyme with an affinity for bones.…”
Section: Introductionmentioning
confidence: 99%